2019
DOI: 10.1097/ta.0000000000002149
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury may worsen clinical outcomes after prolonged partial resuscitative endovascular balloon occlusion of the aorta in severe hemorrhagic shock model

Abstract: Background: The use of partial resuscitative endovascular balloon occlusion of the aorta (pREBOA) in combined hemorrhagic shock (HS) and traumatic brain injury (TBI) has not been well studied. We hypothesized that the use of pREBOA in the setting of TBI would be associated with worse clinical outcomes. Methods: Female Yorkshire swine were randomized to the following groups: HS + TBI; HS + TBI + pREBOA; and HS + pREBOA, (n=5/cohort). Animals in the HS + TBI group were left in shock for a total of 2 hours, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…In this review, two studies included euvolemic animals treated with REBOA as controls. 17,25 A majority of the remainder included only controlled hemorrhage, with severity of hemorrhage ranging widely including variables between 10% and 40% estimated blood volume, 36 25%, 23,27,31,37 35%, 33 40% 17,28,30,35 of estimated blood volume. Two studies report partial REBOA with a goal of proximal SBP: 50 mmHg 32 or 90 mmHg.…”
Section: Preclinical Partial Reboa Researchmentioning
confidence: 99%
“…In this review, two studies included euvolemic animals treated with REBOA as controls. 17,25 A majority of the remainder included only controlled hemorrhage, with severity of hemorrhage ranging widely including variables between 10% and 40% estimated blood volume, 36 25%, 23,27,31,37 35%, 33 40% 17,28,30,35 of estimated blood volume. Two studies report partial REBOA with a goal of proximal SBP: 50 mmHg 32 or 90 mmHg.…”
Section: Preclinical Partial Reboa Researchmentioning
confidence: 99%
“…In animal studies, pREBOA performed to allow titrated and controlled low-volume aortic flow distal to the site of occlusion resulted in physiological patterns similar to baseline, with smaller increases in the intracranial pressure and proximal mean arterial pressure, and did not aggravate TBI, although prolonged pREBOA may worsen the severity of shock [9,13].…”
Section: Discussionmentioning
confidence: 94%
“…To address this knowledge gap, Shackford et al (10) used a porcine model of cryogenic brain lesion and aortic cross clamping to show no adverse effects on ICP, cerebral blood flow (CBF), or water content. These results were replicated with a controlled cortical impact model and expanded to show no worsening of hemorrhage progression in adult swine (11,12). However, Williams et al (12) demonstrated that TBI may worsen the effects of hemorrhagic shock.…”
Section: Introductionmentioning
confidence: 87%